ACTIVE READING STRATEGIES (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Active reading strategies involve purposefully engaging with text through actions like annotating, questioning, summarizing, predicting, and connecting ideas to improve comprehension and retention, moving beyond passive reading by marking up texts, asking "who, what, why," visualizing, and connecting to prior knowledge. Key techniques include previewing text, paraphrasing complex ideas, and reviewing material by explaining it to others or self-testing. There are many different active reading strategies. Each strategy has a specific purpose, but students can use these strategies in tandem to fully understand a text. Some active reading strategies include looking for the author’s purpose, reading and thinking aloud, annotating, making predictions, chunking, questioning, clarifying, using references, and summarizing. Active reading strategies are described below.